A comparison of two Tai Chi interventions tailored for different health outcomes. (June 2021) - Wu, Yin; Senk, Cindy; Coll, Patrick; Glenney, Susan; Zaborowski, Ken; Fortinsky, Richard; Taylor, Beth; Park, Crystal; Benson, Kirsten; McGowan, Matt; DiBiasi, Slyvia; Chen, Ming-Hui; et al.
Highlights: Investigators tailored and compared Tai Chi for two priorities of healthy aging included lowering blood pressure and improving balance. No differences were observed in the effectiveness of lowering blood pressure or improving balance between the two Tai Chi interventions. Tai Chi interventions improved balance, functional fitness and blood pressure of a group of highly physically active older adults. Abstract: Objectives: We compared the health benefits of two different Tai Chi interventions tailored for improving blood pressure (BP) (PRESSURE) or balance (BALANCE). Design: randomized controlled trial. Setting: Community dwelling older adults (≥60yr) practiced Tai Chi at the fitness center of a continuous care community. Interventions: We tailored PRESSURE to emphasize breathing techniques and mental relaxation and BALANCE to emphasize movement principles that challenged balance. Subjects were randomized to PRESSURE ( n = 12), BALANCE ( n = 13), or CONTROL ( n = 10). Tai Chi was practiced 3 sessions/wk, 60 min/session for 12 wk. CONTROL performed normal daily activities. Main outcome measures: We compared the change in cardiometabolic health, balance, and functional fitness between groups with ANCOVA using baseline values, age, and body mass index as covariates. Results: Subjects were physically active, Tai Chi naive (97.1 %), white, mostly female (82.9 %), and older (78.9 ± 5.7 yr) with resting systolic BP (SBP) of 126.5 ± 14.4 mmHg and diastolic BP of 69.3 ± 8.4 mmHg. PRESSURE significantly improved Chair Sit-to-Stand Test (CSTS) (1.0 ± 1.8 vs.−0.6 ± 0.8times/30s, p = 0.03) versus CONTROL, and gait speed (12.8±43.3 vs.−24.1±22.4cm/sec, p = 0.02) versus BALANCE. Meanwhile, BALANCE significantly improved Single Leg Stance Test (5.4±18.0 vs.−8.2±10.3 s, p = 0.049) and CSTS (1.0±1.7 vs.−0.6±0.8times/30s, p = 0.03), and tended to lower SBP (-4.2±16.0 vs. 3.5±8.3mmHg, p = 0.052) versus CONTROL. Conclusion: Within 3 months, Tai Chi improved several health outcomes independent of the type of practice among physically active, Tai Chi naive older adults. Therefore, healthcare and exercise professionals may recommend Tai Chi to physically active older adults without specifying the type of practice.